THE LANGUAGE OF THE “LIVING LIGHT”: SEMIO-BIO-PHOTONICS, ANOTHER EMERGENT APPROACH - Stanciulescu, Traian D.; Nilaya, Shanti (Advances in Social Sciences Research Journal, 2021)
The intention of the present paper is to propose an original connection between semiotics and biophotonics, the unconventional discipline considered as the study of the “ultraweak delayed bioluminescence” emitted by all the living systems (Popp, 1989). The synergy of semiotics and biophotonics − able to assume scientifically the language of the “living light” − is representing the strategy already named by authors Semio-Bio-Photonics (SBPh: Stănciulescu, Nilaya, 2017). In order to define it, the paper is briefly describing and justifying the SBPh scenario of the consciousness and implicitly of (verbal) language genesis. So, the purpose of the present synthesis is to finally recognize that a SBPh integrative approach is indeed possible and necessary for understanding who the real homo significans and homo loquens is.